Increasing the Cooperation Understanding of Students through Project-Based Learning Methods on Social Studies Subject in 3rd Grade SDN Pulogebang 06 Morning East Jakarta (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to determine the application of project-based methods in increasing students' understanding of cooperation. This research was conducted at SDN Pulogebang 06 Pagi, East Jakarta, with 20 students as the research subjects. This research uses classroom action research from Mc. Taggart performed over two cycles. Each cycle consists of the planning stage, action implementation, observation and reflection. The process of collecting data through questions, observations, and observation sheets of the implementation of project-based methods using teacher and student observation sheets, and the results of documentation in the form of photos. The results showed an increase in students' understanding of cooperation using project-based methods. This is evidenced by the results of the initial questions on understanding student cooperation 25%, cycle I 50%, while in cycle II the assessment of understanding of cooperation reached 100%, and teacher activity in cycle I 75% and students 77.7%, in cycle II the presentation of teacher results and students 100% (mastery learning). The implications of this study indicate that the use of project-based methods can improve students' understanding of cooperation seen from an increase in the value of each cycle, therefore teachers need to innovate in developing the learning process so that the learning process becomes dynamic and meaningful.